Does psychosocial stress experienced at different points across the rat lifespan cause sex-specific changes in spatial learning and memory and plasticity-related proteins? - Davari Dowlatabadi, Saeideh (University of Waterloo, 2023)
Overview Considering that susceptibility to a range of diseases appears strongly influenced by both sex and exposure to social stress, there is a need to evaluate how adverse experiences across the lifespan (alone and in combination) may affect brain development and function, and whether these interactions are modified by sex. Therefore, we examined two models of social stress, Chronic Early-Life Social Isolation (CELSI; an early-life psychosocial stressor) and Bystander Stress (ByS; an adult psychosocial stressor), individually and together, to determine how they affected the hippocampus (a structure important for learning and memory) in both male and female rats. Objectives Various models have been proposed to help explain how early-life and adulthood stressors interact to affect disease vulnerability. In particular, the match/mismatch hypothesis suggests that early-life experiences can most clearly affect disease risk when they are incongruent with experiences during adulthood. However, since we had insufficient background information about the individual effects of the selected psychosocial stress models (especially the ByS model), we began by exploring some of the critical behavioural and biochemical traits of CELSI and ByS models in both male and female rats. After this, we examined the potential impact of post-weaning chronic social isolation on hippocampus-dependent behavioural and biochemical responses to bystander stress in adulthood. Potential changes in spatial learning and memory performance were evaluated along with changes in the expression of several glutamate receptor subunits (including GluA1, GluA2, GluN1, GluN2A, and GluN2B) and PSD-95 in the septal and temporal poles of the hippocampus. The highlighted proteins were selected given that they are upstream elements of hippocampal synaptic plasticity and play an important role in learning and memory. Importantly, all assessments of the behavioural and biochemical data were done using sex as a variable. Methods For the first study, upon weaning, male and female siblings from 15 Sprague-Dawley rat litters were stratified by sex and then randomly assigned to either group housing (3 animals/cage), or social isolation (1 animal/cage) for 7 weeks (that is, CELSI). Spatial learning and memory were then tested over 5 days using the Morris water maze (MWM). Next, the animals were euthanized, and a variety of stress-sensitive biometrics (body weight, adrenal gland weight, liver weight, retroperitoneal fat pad weight, serum corticosterone levels, liver lipid content, and non-fasting blood glucose) were collected. Lastly, to determine whether CELSI affected neural cell density, the expression of key neuronal and glial proteins (PSD-95 and GFAP, respectively) was assessed in isolated hippocampal tissue using Western blotting. In the second study, bystander stress was applied to adult male and female rats twice per day for 5 consecutive days. To remove the potential influence of behavioural testing on the expression of plasticity-related proteins in the hippocampus, the study was completed in two parts: 10 groups were examined using the MWM and 6 groups were used for tissue harvesting after the stress paradigm. Following the hippocampal dissection, septal and temporal poles were isolated. Then, after preparing enrichments of synaptic terminals, Western blotting was used to measure the expression of key AMPA and NMDA receptor subunits (GluN1, GluN2A, GluN2B, GluA1, and GluA2), as well as PSD-95. In the final study, to investigate the effect of early-life stress on response to adulthood stress (by considering match/mismatch theory), after undergoing CELSI (or group housing), animals were placed in standard housing conditions for 6 months and then underwent ByS. Once the ByS paradigm was completed, MWM data were collected. After the collection of behavioural data, hippocampal tissue was harvested, synaptoneurosomes were prepared, and Western blotting used to examine the expression of AMPA and NMDA receptor subunits, as well as PSD-95, in the septal and temporal poles. Results Unexpectedly, in study one, socially isolated male and female rats displayed stronger spatial learning and memory ability than group housed rats. As well, socially isolated male rats exhibited increased expression of PSD-95 (a key neuronal cell marker). However, there was no clear effect of housing condition on stress-sensitive biometrics, or the hippocampal expression of GFAP. In study two, no significant differences were observed between the spatial learning and memory performance of control and bystander stress male and female rats. However, the expression of GluA2, GluN2A, and GluN2B was dramatically decreased in the septal pole of the hippocampus in male rats exposed to bystander stress, when compared to male bystander control rats. In contrast, levels of GluA2 were clearly increased in the temporal pole of the hippocampus from female ByS rats compared to female ByC rats. Lastly, expression of PSD-95 was found to be greater in the temporal pole of male ByS rats relative to female ByS rats. The results of study three indicate that male rats performed better on the spatial learning task than female rats within the matched control situation (group housing during the post-weaning period followed by the ByC group during adulthood). Surprisingly, the learning performance of male animals that experienced the mismatch 1 condition was also superior to that of female animals (that is, the animals underwent social isolation followed by ByC). In alignment with our hypothesis, male animals exposed to a stressful situation both during development and in adulthood (that is, with matched stress exposures: SI-ByS) displayed better spatial learning on day four than animals that were raised in group housing, but experienced bystander stress in adulthood (a mismatched situation: GH-ByS). In terms of protein expression, a significant increase in GluN1 expression was observed in the hippocampal septal pole of male rats exposed to matched stressful situations (SI-ByS) as compared to matched control male rats (GH-ByC). Conclusion Our findings reveal that there are sex-based, long-standing effects of early-life adversity on later stress exposure with regards to hippocampal-dependent behaviour. In particular, our results indicate that spatial learning performance was best on the match condition on adversity (SI-ByS), but only in male rats. The finding supports the match/mismatch theory in that the outcome from dealing with an adult psychosocial stressor similar to the environment encountered during early life (match) differs from that observed when dealing with incongruent psychosocial situations encountered across the lifespan (mismatch) and, notably, that male and female rats are uniquely affected.
Keywords: chronic early life social isolation; bystander stress; match/mismatch theory; spatial learning and memory